2019
DOI: 10.1101/798595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the genome-wide contribution of selection to temporal allele frequency change

Abstract: AbstractRapid phenotypic adaptation is often observed in natural populations and selection experiments. However, detecting the genome-wide impact of this selection is difficult, since adaptation often proceeds from standing variation and selection on polygenic traits, both of which may leave faint genomic signals indistinguishable from a noisy background of genetic drift. One promising signal comes from the genome-wide covariance between allele frequency changes observable from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 63 publications
2
68
0
Order By: Relevance
“…As polygenic adaptation in quantitative traits is likely ubiquitous, our conclusions have potentially important implications. One is that, contrary to adaptation mediated by selective sweeps of initially rare, large effect, beneficial alleles (Smith and Haigh, 1974; Kaplan et al, 1989; Braverman et al, 1995; Hermisson and Pennings, 2005; Coop and Ralph, 2012; Berg and Coop, 2015), polygenic adaptation might have minor effects on patterns of neutral diversity at any given point in time (but may affect temporal diversity patterns (Buffalo and Coop, 2019, 2020). The effects of selected alleles on neutral diversity at linked loci follow from their trajectories (Barton, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As polygenic adaptation in quantitative traits is likely ubiquitous, our conclusions have potentially important implications. One is that, contrary to adaptation mediated by selective sweeps of initially rare, large effect, beneficial alleles (Smith and Haigh, 1974; Kaplan et al, 1989; Braverman et al, 1995; Hermisson and Pennings, 2005; Coop and Ralph, 2012; Berg and Coop, 2015), polygenic adaptation might have minor effects on patterns of neutral diversity at any given point in time (but may affect temporal diversity patterns (Buffalo and Coop, 2019, 2020). The effects of selected alleles on neutral diversity at linked loci follow from their trajectories (Barton, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach is subject to many of the caveats discussed below in that it assumes a constant population size and the model would be violated by migration or other temporal variation in population composition. Therefore, although this approach is supported by simulations, and has been demonstrated to be effective at estimating temporal covariance in allele frequencies associated with linked selection in lab‐based experimental evolution (Buffalo and Coop 2019a, b), it may be limited in its application to real‐life aDNA data. The effect of population stratification on polygenic signals from modern samples has recently been highlighted, when two studies found that the signal for height selection in Europe was less pronounced in the U.K. Biobank dataset, which is less confounded by population structure than the GIANT consortium dataset (Berg et al.…”
Section: Detecting Polygenic Selection On a Polygenic Traitmentioning
confidence: 99%
“…Genome-wide analyses have identified polymorphisms and inversions that oscillate in seasonal timescales in several localities in the United States and Europe (Bergland et al 2014; Kapun et al 2016; Machado et al 2018). However, a recent analysis suggested seasonal fluctuations in allele frequencies seems small and temporal structure independent of seasons may be more important in this system (Buffalo and Coop 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying polymorphisms that fluctuate seasonally is challenging, because effect sizes are small and populations are subject to stochastic environmental events that are not tied to seasonality (Machado et al 2018). Indeed, a recent study put in question the interpretation that a set of previously identified seasonal SNPs in D. melanogaster is due to seasonally varying selection (Buffalo and Coop 2019).…”
Section: Introductionmentioning
confidence: 99%